Gemfibrozil Reduces Plasma Prothrombin Fragment F1+2 Concentration, a Marker of Coagulability, in Patients with Coronary Heart Disease - Wilkes, H C; Meade, T W; Barzega, S; Foley, A J; Hughes, L O; Bauer, K A; Rosenberg, R D; Miller, G J (Thrombosis and Haemostasis, 1992)
The effects of gemfibrozil on several indices of haemostatic activity were explored in male patients with coronary heart disease (CHD). Sixty-three of 71 patients completed a crossover study in which gemfibrozil 1,200 mg/day and matching placebo were each taken in randomised order for 2 months in a doubleblind manner, separated by a 2-month washout period. Serum cholesterol decreased by an average (95% confidence interval) of 12 (9 to 15)% and non-fasting triglyceride concentration by 43 (34 to 51)% during active treatment. Plasma prothrombin fragment Fi+ 2 concentration, a marker of the in vivo rate of generation of thrombin, was 25 (12 to 37)% lower on average while on gemfibrozil than during the placebo phase. Factor VII coagulant activity (VIIC) and antigen concentration, and fibrinopeptide A concentration were not influenced by gemfibrozil in the group overall. However, the VIIC response appeared to be dependent upon the untreated cholesterol level. Hypercholesterolaemic men (cholesterol >6.5 mmol/1) experienced a significant reduction in VIIC averaging 6% of standard during active therapy. Other effects of gemfibrozil were a 5 (2 to 9)% increase in plasma fibrinogen by a gravimetric method, an 11 (8 to 13)% increase in platelet count, and a 6 (2 to 10)% reduction in white cell count. The reduced incidence of CHD following gemfibrozil therapy in hyperlipidaemic patients may arise in part through a reduction in procoagulant activity and thus the risk of an occlusive coronary thrombosis.